Inner Strength of Female Characters in Loitering with Intent and The Public Image by Muriel Spark - Rogalińska, Monika (Text Matters: A Journal of Literature, Theory and Culture, 2011)
Women characters in Muriel Spark's novels are diverse, some strong and powerful, some weak and unable to make decisions. And there are characters who develop throughout the novel and learn from their own mistakes. From being passive, they gradually start acting and making their own choices. Loitering with Intent and The Public Image present women characters who go through metamorphosis, from being dependent on others into living their own lives and freeing themselves from former influences. Such kaleidoscopic change enables them not only to be able to finally make their own decisions but also to overcome many difficult situations threatening their future life. Fleur Talbot, a heroine in Loitering with Intent, finds herself at a point in which she thinks that everything she cares for is lost. Chronically passive and naïve, she cannot imagine another way of being until she understands that she is being cheated, that her life will be ruined if she does not act. Everyone around her seems to be in conspiracy against her; only taking a firm stand and opposing her surrounding world can help. Fleur's life has become totally dependent on her ability to be strong and decisive. She knows that if she remains what she is, her career and prospects for the future will be lost, so she decides to prove her determination and her will to be finally happy. Her transformation into a powerful character saves her dignity and makes her a successful writer. Annabel, a character in The Public Image is the same type of person as Fleur, as she lacks self-confidence and has no support from anybody, even her own husband. Muriel Spark, however, presents her as another example of a heroine who develops as the action progresses, able to evoke strength in herself when her situation seems hopeless. Annabel, at first treated as a puppet in the hands of other people, who use her image for their own benefit, shows that she is capable of anything by the book's end. When her career and reputation are threatened and her privacy invaded, she decides to leave the country. This requires both effort and sacrifice, as she has to leave behind everything she has worked for all her life, but this is the necessary price for her freedom. The ability of both female characters to show so much determination reveals an inherent inner strength, and their weakness and vulnerability as just superficial. When the situation requires it, both Annabel and Fleur are ready to fight for their rights, for their freedom and self esteem, and they discover that they are indeed capable of changing their lives.